2010
DOI: 10.1007/s10311-009-0273-3
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for effect of soil compaction on the degradation and impact of isoproturon

Abstract: Soil is damaged by several threats and, among them, chemical contamination by pesticides and compaction. However, the effect of compaction on the fate of pesticides in soil, and the impact of pesticides on soil biological functioning are unknown. Therefore, we studied the effect of soil compaction on the degradation of the herbicide isoproturon, and the impact of this herbicide on an enzyme activity (b-glucosidase) involved in the C soil cycle. Undisturbed soil samples were prepared at different bulk densities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
5
12
0
Order By: Relevance
“…The presence of fresh organic matter originating from urban waste compost did not modify the observed results. This was consistent with the results of Mamy et al (2011) who showed that, in the conditions of the experiment, soil compaction did not modify significantly the degradation of isoproturon, neither the formation rates nor the nature of its metabolites. Spatial localization of microorganisms.…”
Section: Effect Of Soil Structure On the Degradation Of Pesticides Insupporting
confidence: 93%
See 2 more Smart Citations
“…The presence of fresh organic matter originating from urban waste compost did not modify the observed results. This was consistent with the results of Mamy et al (2011) who showed that, in the conditions of the experiment, soil compaction did not modify significantly the degradation of isoproturon, neither the formation rates nor the nature of its metabolites. Spatial localization of microorganisms.…”
Section: Effect Of Soil Structure On the Degradation Of Pesticides Insupporting
confidence: 93%
“…The integrative measurable parameters at this scale are the bulk density and the water content of soil samples. Our recent results confirm that this scale is suited to study the effects of soil structure on the fate of pesticide (Mamy et al, 2011). This scale is also appropriate to measure, in an integrative manner, the fate and ecotoxicological impact of pesticides in conditions close to the field ones.…”
Section: Relevant Scale and Influent Integrated Factorssupporting
confidence: 75%
See 1 more Smart Citation
“…However, the capacity of soil to perform its broad variety of crucial functions might be reduced, mainly due to chemical contamination by pesticides (Mamy et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of soil structure in soil quality has been recognized for many years because it affects transport phenomena as well as biological activity inherent to soil organic matter dynamic (Six et al, 2004), or to the fate of organic contaminant (Mamy et al, 2011). The structure of soil depends on soil texture and organic matter (Carter, 2004;Dexter, 2004aDexter, , 2004b.…”
Section: Introductionmentioning
confidence: 99%